The Influence of 'Fear of Success' and 'Need for Achievement' on the Vocational Aspirations of Male and Female High School Studentsk - Crealock, Carol (Canadian Journal of Counselling and Psychotherapy, 2012)
Fifth year high school students responded to questionnaires measuring need for achievement and fear of success and indicated their future occupational and educational aspirations. The female students were found to aspire to less demanding occupations than the male students and both motivational constructs predicted vocational aspiration.